PTH-010 Are anticoagulant and antiplatelet medications restarted appropriately after an upper GI bleed?. (June 2019) - Creamer, John; Ben Arnold, Melanie Cuffe; Perry, Rachel; Robinson, Anya; DiMambro, Alex
Abstract : Introduction: Failure to restart anticoagulant and antiplatelet medication appropriately after achieving haemostasis following an upper gastrointestinal bleed (UGIB) is associated with an increased risk of cardiovascular events and higher patient mortality 1 . This audit aimed to look at how long such medication was held for against NICE and the European Society of Gastrointestinal Endoscopy (ESGE) guidelines 2 which suggest aspirin should be continued immediately post-haemostasis and warfarin/direct oral anticoagulants (DOACs) restarted after 7–15 days. Methods: Electronic records were reviewed to identify all inpatient OGDs performed for suspected UGIB between 1st January and 31st December 2018 in patients taking anticoagulant or antiplatelet medication. Individual records were scrutinised to review the duration agents were held and whether a recurrent UGIB or cardiovascular event occurred within 90 days. Cases with no confirmed bleeding at endoscopy and low clinical suspicion of UGIB were excluded. Results: There were 26 confirmed UGIB in patients taking aspirin, of which 6 (23%) had aspirin continued immediately post-haemostasis. Of the remaining 20 patients, only 9 (45%) had clear documentation as to why aspirin was stopped or held longer. There were 41 cases of UGIB in patients on anticoagulation (8 on warfarin, 33 on DOACs). In 12 cases a clear decision was documented to stop anticoagulation long-term. One patients' records were unavailable. In the remaining 28 patients, 6 (21%) had anticoagulation re-started at 7–15 days post haemostasis, while 14 (50%) had anticoagulation re-started earlier than this. Five patients had a further UGIB within 90 days, which was associated with age (80% over the age of 80) and early reintroduction of anticoagulation (40%). 80% of repeat bleeds occurred on rivaroxaban, consistent with data suggesting it may have a higher risk of GI bleeds in elderly patients. Conclusions: Every UGIB is unique and generic guidelines will not always apply for valid clinical reasons. However, failure to follow such guidelines when appropriate leads to an increased risk of adverse events and documentation of reasons for deviating from clinical guidelines is often inadequate. The introduction of a national GI bleed proforma to remind physicians of guidelines and allow clear documentation of decisions regarding anticoagulant or antiplatelet medication may improve compliance and reduce morbidity post-UGIB. References: Radelli F, et al. Management of anticoagulation in patients with acute gastrointestinal bleeding. Digestive and Liver Disease 2015:621–627. Gralneck I, et al. Diagnosis and management of nonvariceal upper gastrointestinal haemorrhage: ESGE Guidelines. Endoscopy 2015;47:1–46.